(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
Regarding defining the electoral districts for the elections of the General National Congress to select 200 members of the General Conference, the National Transitional Council issued Law No. (14) of 2012 AD, which divided Libya into main electoral districts that include 13 electoral districts comprising 73 sub-electoral districts, and the number of individual districts reached 69 Sub-constituency While the 73 districts were grouped into 20 existing electoral districts, the electoral system confirmed under the 2012 Constitutional Declaration and according to Law No. (4) of 2012 regarding the election of the General National Congress, and clarified that the division of electoral districts was carried out according to the criteria of geographical area and population , but it did not include any detailed provisions, and there is a lack of clarity regarding the distribution of seats according to the main and subsidiary electoral districts, and there is also a discrepancy in the distribution of administrative components and polling stations at the level of the regions of the main districts, and therefore it was better to reconsider defining the electoral districts and taking into account the rapprochement between the population and the number of voters and respect for the administrative groupings and the geographical boundaries of each district.